A THEMATIC LITERATURE REVIEW ON SUKUK - Fareiny Morni (Jurnal Internasional Ekonomi Islam, 2019)
Although there has been extensive research being done in the field of Islamic finance, literature on sukuk are inadequate. This paper intends to present a thematic review of this subject matter. Through a thematic and chronological review, this paper is divided into the following themes; the first two sections are general i.e. we begin with an overview on the structure and nature of a sukuk contract, and the theories that have been adopted in sukuk research. While the remaining sections are separated according to the type of research i.e. a comparison between sukuk and bonds and investors’ perception of sukuk, and the impact of sukuk on economic growth. Besides providing a summary of the main points covered in current literature, this paper also highlight trends and issues on sukuk research and provide insight on limitation of current research as well as suggest future research directions.